Réponses

2014-01-28T14:35:50+01:00
Bonjour

A = 3(x + 2) + (7+ 4x) (7 - 6x)
   = 3x + 6 + 49 - 42x + 28x - 24x²
   = -24x² - 11x + 55


B = 4(x + 9) - (7 + x)(x + 1)
   = 4x + 36 - (7x + 7 + x² + x)   
   = 4x + 36 - 7x - 7 - x² - x
   = -x² - 4x + 29

C = -2(1 - 3x) - (3x + 2) (x - 5)
    = -2 + 6x - (3x² - 15x + 2x - 10)
    = -2 + 6x - 3x² + 15x - 2x + 10
    = -3x² + 19x + 8


D = -3(a² + 2) - (a - 3) (2a + 7)
    = -3a² - 6 - (2a² + 7a - 6a - 21)
    = -3a² - 6 - 2a² - 7a + 6a + 21
    = -5a² - a + 15